International Outcomes of the Boston Type I Keratoprosthesis in Stevens–Johnson Syndrome. Issue 11 (November 2015) - Alexander, Jamie K.; Basak, Samar K.; Padilla, Ma. Dominga B.; Yu, Fei; Aldave, Anthony J.
Abstract : Purpose: To determine the factors influencing outcomes of Boston type I keratoprosthesis implantation in Stevens–Johnson syndrome (SJS) and to compare the results with those of individuals without SJS. Methods: This is a multicenter, retrospective, comparative consecutive case series of patients undergoing keratoprosthesis implantation in Los Angeles, Kolkata, and Manila. Statistical analysis was performed to identify significant differences in visual acuity, complications, and retention between SJS and non-SJS populations. Results: A total of 234 keratoprosthesis procedures were performed in 209 eyes, including 40 performed in 27 eyes of 26 patients with SJS. Procedures in patients with SJS were more frequently performed as repeat keratoprostheses (33% vs. 8%, P < 0.001) but less frequently in eyes with glaucoma (26% vs. 71%, P < 0.001) or multiple previous keratoplasties (15% vs. 59%, P < 0.001). A significantly greater percentage of individuals with SJS had a corrected distance visual acuity ≥20/200 12 months after surgery compared with individuals without SJS (100% vs. 67%, P = 0.002). Several postoperative complications were more common in SJS, including corneal stromal necrosis (59% vs. 8%, P < 0.001), corneal infiltrates (30% vs. 10%, P = 0.009), and persistent corneal epithelial defects (59% vs. 24% P < 0.001), which led to a higher retention failure rate (0.306/eye-year vs. 0.068/eye-year, P < 0.001) and secondary surgical procedures. However, after repeat implantation, eyes with SJS were no less likely to ultimately retain a keratoprosthesis (82% vs. 89%, P = 0.34). Conclusions: The Boston type I keratoprosthesis is an effective means to restore vision in individuals with SJS. Although retention failure and several postoperative complications are more common in SJS, sight-threatening complications such as endophthalmitis and retinal detachment are not. Abstract : Supplemental Digital Content is Available in the Text.